Managed code rootkits : hooking into runtime environments - Metula, Erez (Syngress, 2011)
"Introduces the reader briefly to managed code environments and rootkits in general--Completely details a new type of rootkit hiding in the application level and demonstrates how a hacker can change language runtime implementation--Focuses on managed code including Java, .Net, Android Dalvik, and reviews malware development scenarios"--Provided by publisher.